Mechanisms of milk gel formation and applications in food products – A Review - Shiby, Varghese K; Tabassum, Aisha; Pandey, Mohan C (Indian Journal of Dairy Science, 2016)
Abstract  The gelation of proteins can be considered as protein solutions transformed into the gels, which is facilitated by heat, enzymes, or divalent cations under appropriate conditions.  The gels of milk proteins are usually classified as particle gels, which are irreversible in contrast to many polysaccharide gels that are thermo reversible.   The formation of which is affected by various factors including ratio and type of milk, solids content, heating, acidification, glucuno–δ-lactone (GDL), lipids , rennet and fermentation by lactic cultures. Milk proteins, especially whey proteins, have found many applications in food product formulations. The research studies on functional properties of proteins have been generally performed on model systems to optimize their effects. The applications of whey protein gels in various food products including dairy and meat products have been briefly discussed and the mechanism of gel formation is elucidated in this review.